(untitled) (Research, Society and Development, 2025)
Hospital Dentistry has established itself as a fundamental specialty in the care of hospitalized patients, especially those in Intensive Care Units (ICUs) and with complex clinical conditions. This article discusses the relevance of the dentist’s role in the hospital setting, with na emphasis on the prevention and control of oral and systemic infections associated with oral health. Scientific evidence shows that adequate oral hygiene and dental follow-up during hospitalization are directly related to the reduction of infectious complications, such as ventilator-associated pneumonia (VAP), bacterial endocarditis, and sepsis. The integration of dentistry into the multidisciplinary hospital team is, therefore, na essential strategy for patient safety and the promotion of integrated and humanized healthcare.